The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1115/1.2903845
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Rotating Bladed Disk Forced Response Using Underplatform Friction Dampers

Abstract: In this paper, we present a methodology and results from an experimental investigation of forced vibration response for a bladed disk with fitted underplatform “cottage-roof” friction dampers, together with the corresponding numerical predictions. A carefully designed and constructed rotating test rig is used to make precise measurements, which involve only the phenomena of interest. For this purpose, the measurement rig is operated under vacuum to eliminate aerodynamic effects on the rotating blisk and noncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Several studies on friction damping in bladed disks have been presented in the literature. Most of these focus on friction damping in bladed disks assemblies [2,6,12,14]: under-platform dampers, shrouds, blade-root damping,. .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on friction damping in bladed disks have been presented in the literature. Most of these focus on friction damping in bladed disks assemblies [2,6,12,14]: under-platform dampers, shrouds, blade-root damping,. .…”
Section: Introductionmentioning
confidence: 99%
“…In recent developments [34,35], a specific test rig was designed to measure the forces transmitted between the damper and the platform, as well as the relative displacements, allowing a fine tuning of the contact parameters when compared to the simulations. More realistic set ups have been proposed [36,37], but they tend to introduce additional complications such as uncertainties about the damper position during operation, and mistuning due to the bladed disk manufacturing tolerances. The asymmetry of the excitation system used in the double beam configuration could lead to potential mistuning as well, but with the damper in place, no double peak response was observed for the analysed modes.…”
Section: Rig Concept and Non-dimensional Parametersmentioning
confidence: 99%
“…Two pseudo beam-like blades are fixed on a common base, which simulates a rigid disk. For this investigation, the damper is a wedge-type, [36], which has a triangular cross section with a characteristic angle. Unlike in a real high-pressure turbine blade, the aerofoil is substituted by a straight rectangular cross-section beam.…”
Section: Rig Concept and Non-dimensional Parametersmentioning
confidence: 99%
“…A single-harmonic balance approach [25] was considered for this study, but it was found to be unable to capture the complex behavior occurring at the interface [59,60]. Therefore a multi-harmonic balance solver, which forms part of the software code, FORSE (Forced Response Suite) [37][38][39], developed at Imperial College London for industrial scale use [44,61], was used.…”
Section: Mathematical Backgroundmentioning
confidence: 99%